HUBUNGAN FAKTOR SOSIODEMOGRAFI TERHADAP STATUS GIZI ANAK SD NEGERI 1 PRINGSEWU SELATAN - Dyah Wulan Sumekar RW; Diana Mayasari; Mukhlis Imanto; Isnida Shela Arlovi (CV. Jasa Sukses Abadi, 2021)
Nutrition plays an important role in children health. The prevalence of underweight children in Indonesia by 11.2% to 4.0% was very thin and emaciated 7.2%, while the obese children by 18.8%, consisting of 10.8% obese children and obese amounted to 8.8%. Lampung Province was ranked second among the provinces with a skinny kid. The nutritional status itself can be affected by several things, one of which is the status of demographics. The purpose of this study is known association of sociodemographic factors with nutritional status of children. This type of research is an analytic observational with cross sectional approach. The population is students of SDN 1 South Pringsewu, with a sample size of 225 people. The statistical test used was chi - square. The results of the univariate analysis are mostly had normal nutritional status (68%), age 6-9 years (75.6%), female (51.1%), highly educated mothers (77.3%), father's occupation were self-employed (64%), parents have a high income levels (> Rp. 1.581 million) (69.3%). The results of the bivariate analysis obtained no relationship between maternal education level (p-value < 0.001), the type of father's occupation (p-value < 0.001), and the level of family income (p-value < 0.001) with the nutritional status of children. While there is no correlation between age (p-value = 0.829), and the child's gender (p-value = 0.307) with the nutritional status of children. Expected the school to coordinate with health officials in monitoring the nutritional status of their students. Keywords : Sociodemographic, nutritional status of children